Educação em saúde na prevenção de síndromes hipertensivas na gravidez - Viana, Larissa Fernandes (Brasil, 2023)
Introduction: Hypertensive syndromes are one of the main causes of maternal and perinatal morbidity and mortality, diseases that most frequently complicate pregnancy, affecting 5% to 10% of pregnancies, and are a worldwide public health problem and the 1st in Brazil, in view of this reality, some studies demonstrate that the educational activities carried out during the pregnancy-puerperal cycle are essential for the prevention of cardiovascular diseases and other complications during pregnancy. Objectives: To identify health education actions carried out during prenatal care to prevent hypertensive syndromes. Methodology: The research is a descriptive, exploratory study of the prospective type, with a qualitative approach, the theoretical method of thematic analysis of content proposed by Minayo was used, carried out with 40 pregnant women, over 18 years old, who were doing the pre -natal, from July 2022 to March 2023, at USF Dr. Luiz Montenegro, located in the South Zone of Manaus. Results: Prevailed participants aged between 19 and 30 years old, single, complete high school, brown, family income of 1 minimum wage, none of the participants had arterial hypertension and/or diabetes mellitus. In the face of the interviews, 16 pregnant women reported that they were not instructed about the risks of high blood pressure, but the common recommendation for them was a change in diet and only 16 participants knew what Health Education is. Conclusion: Practices aimed at health education need improvements in prenatal care, as pregnant women consider these practices fundamental, it is believed that this study serves to contribute to the reflection of health professionals who work in care and in management.